A novel approach for the determination of freshness and identity of trouts by MALDI-TOF mass spectrometry. (October 2017) - Ulrich, Sebastian; Beindorf, Philipp–Michael; Biermaier, Barbara; Schwaiger, Karin; Gareis, Manfred; Gottschalk, Christoph
Abstract: Properly handled fish is usually marketed as "fresh fish" until day 10 after fishing. About 40% of the total fishery that is used for direct human consumption is marketed in fresh form stored at temperatures up to +2 °C. Currently, there are no validated methods available for controlling the recommended period of storage. Apart from being a potential source for food fraud, spoiled fish represents a major source of foodborne illnesses and intoxications. In this study, a rapid MALDI-TOF mass spectrometry based screening method was developed using the vitreous fluid of fish eyes as specimen for the examination of different days of storage. The vitreous fluid was collected from n = 100 freshly fished brown trouts at day 0, 3, 7, 9, and 11 post mortem (n = 20 brown trouts each day of examination). The samples were immediately measured by MALDI-TOF mass spectrometry in linear positive mode (mass range m/z 2000–20, 000 Da). For quality assurance the experiment was repeated with a set of brown trouts (n = 100) originating from the same fish farm and with brown trouts (n = 100) originating from a different fish farm. For specificity testing rainbow trouts (n = 10) were examined accordingly. All obtained mass spectra were processed by means of MALDI Biotyper OC 3.1 and ClinProTools 3.0 software. The MALDI Biotyper approach showed limited applicability for the identification of the time of storage. However, it was suitable to reliably discriminate between the closely related species brown and rainbow trout. Processing by ClinProTools revealed four crucial mass peaks ( m/z 2594 Da, m/z 4857 Da, m/z 4879 Da, m/z 4899 Da) which enabled a reliable differentiation between day 0 and 3, 7, 9, 11 (rate of correct identification > 90%) as well as the differentiation between day 3 and 7, 9, 11 (rate of correct identification > 72%). However, this approach showed limited applicability within the end of the tested period of storage when comparing between day 7, 9, or 11. Highlights: Application of the vitreous fluid as sample material. Development of a reliable extraction method for MALDI-TOF MS. Generation of reference mass spectra for closely related trout species. Generation of statistical models for determination of days of storage.